Nilai parameter timpanometri Kanak-kanak Pra-sekolah Normal dan Sindrom Down - Noor Alaudin Abdul Wahab; Wan Fazlina Wan Hashim (penerbit ukm, 2004)
Guidelines for middle ear screening by the American Speech-Language-Hearing Association (ASHA) have suggested the use of quantitative approach for tympanogram interpretation. Compared to the qualitative approach that has been used previously, the quantitative approach is more suitable because it is an objective approach and can be applied with the commercial tympanometer available in the market. This study intended to obtain absolute values of tympanometric characteristics, which are the peak compensated static acoustic admittance (Peak Ytm), tympanogram width (TW) and the external ear canal volume (Vea) in normal preshoolers and Down Syndrome children. Fifteen normal and 12 Down Syndrome children that suited the subject selection criteria have participated in this study. The mean values for Peak Ytm and Vea in normal children were 0.36 mmho and 0.57 cm3 , respectively, while the Down Syndrome children showed mean values of 0.14 mmho and 0.38 cm3. The normal and Down Syndrome children showed TW mean values of 99.73 and 148.65 daPa, respectively. Statistical analysis showed significant difference between the two groups of subject for all three tympanometric parameters obtained in this study.